Effectiveness of Adaptation Mechanisms of Farmers in Flood Prone Area of Bihar (Indian Journal of Extension Education, 2023)
The state of Bihar is most vulnerable to floods in India and farmers in flood-prone areas have undergone adaptation through a combination of technological and institutional innovations. The present study aimed to explore the effectiveness of adaptation mechanisms as perceived by the farmers to mitigate the negative effects of flooding on their livelihoods covering a random sample of 80 farmers in flood-prone areas of Bhagalpur district in Bihar during 2022. The findings suggest that farmers have developed a range of adaptation strategies to cope with the impacts of flooding, the most effective being the changes in cropping patterns, adoption of flood-resistant paddy varieties, pest and disease resistance vegetable varieties, vaccination of livestock and management of fish ponds. Institutional innovations like self-help group, farmers interest group, farmers club, seed bank, village level weather advisories were also found crucial to enabling farmers to adapt to floods. Income, cultivated land, information availability, and use of communication sources have explained about 50 per cent variation in the perceived effectiveness of adaptation by farmers. Future extension efforts need to strengthen the institutional infrastructure to promote the flood resilient technologies to reduce the vulnerability of farm livelihoods.